Literature Review: Glucocorticoid-Induced Osteoporosis (GIOP) Therapy Based on Current Evidence - Atika Ananda Putri; Ida Royani; Prema Hapsari Hidayati (PSPP JOURNALS, 2026)
Glucocorticoid-Induced Osteoporosis (GIOP) is the most common form of secondary osteoporosis resulting from long-term glucocorticoid use and is associated with an increased risk of fracture. The management of GIOP continues to evolve as new evidence emerges regarding pharmacological therapy, sequential strategies, and fracture risk-based approaches. This article aims to review glucocorticoid-induced osteoporosis (GIOP) therapy based on the current evidence. This study is a literature review with a search of articles from the PubMed database between 2023 and 2026. The literature used includes original research, systematic reviews, meta-analyses, and clinical guidelines relevant to glucocorticoid-induced osteoporosis (GIOP). Current evidence suggests that glucocorticoid-induced osteoporosis (GIOP) therapy includes bisphosphonates as first-line therapy, denosumab as an alternative in certain at-risk patients, and teriparatide in high-risk patients. Sequential therapy approaches (anabolic-to-antiresorptive) and treat-to-target strategies have been shown to be more effective in increasing and maintaining bone mass. Current evidence-based therapy for glucocorticoid-induced osteoporosis (GIOP) emphasizes an individualized, risk-based approach with a combination of pharmacological therapy, calcium and vitamin D supplementation, lifestyle modification, and regular monitoring. This comprehensive approach is essential to reduce fracture risk and improve quality of life in patients taking long-term glucocorticoids.